School Self Evaluation Concepts in The Context of Program Evaluation Mobile School - J. Lokollo, Lambertus; Rudolf Kempa; Manunay, J. Marthen (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
Evaluation of the driving school program is important in proving the success or failure of the program. The stages in the evaluation of driving schools consist of the initial program evaluation stage, the mid-program stage and the final program stage. Driving schools must prepare themselves to face the evaluation process according to the intended stages. Self-evaluation is one of the alternative choices that schools can make to assess the school's self-assessment in achieving the driving school program in order to take steps to change on an ongoing basis in order to achieve the goals of the driving school program as stipulated. This research is a descriptive research carried out using the library research method using content analysis (content analysis). Based on information obtained from the literature related to the concept of school self-evaluation, program evaluation and school performance according to the results of the analysis, school institutions through the concept of self-evaluation with an action research approach can be carried out through the stages of preparation, data collection, formulation of evaluation results, planning and implementing change plans . School self-evaluation with this approach can be carried out repeatedly so that significant changes can be made in order to realize improvements so that the results and impact of the driving school program can be felt.